요양병원 간호사의 낙상예방행위에 미치는 영향요인 - 최주연; 이가언; 전혜정 (한국직업건강간호학회지, 2022)
The purpose of this study was to identify factors influencing fall-prevention behaviors of nurses working in long-term care hospitals. Methods: Participants included 147 nurses working in 10 long-term care hospitals in B city. Data were collected from September 20-October 12, 2016. SPSS/WIN 21.0 was used for analysis with t-test, ANOVA, Scheffé test, Pearson correlation coefficients, and multiple regression. Results: It was found that attitude toward fall (r=.29, p<.001) and patient safety culture (r=.25, p=.002) had a significant positive correlation with fall-prevention behaviors of nurses working in long-term care hospitals. The factors influencing fall-prevention behaviors in participants were clinical career and patient safety culture (β=.21, p=.012), contributing to 19% of the total variance in fall- prevention behaviors. Conclusion: The findings showed that systematic delivery of differentiated fall prevention education is preferred to nurse's clinical career as a private factor to improve fall-prevention behaviors of nurses in long term care hospital. Particularly, it is imperative to conduct periodical and practical fall-prevention education for nurses to prevent career discontinuity. An independent report system and open communication system as well as a scheme that can disseminate patient safety culture in individual departments to implement patient direct nursing are required to encourage patient safety culture in organizations.